An adaptive filters based PMU algorithm for both steady-state and dynamic conditions in distribution networks. (May 2020) - Wang, Yinfeng; Lu, Chao; Kamwa, Innocent; Fang, Chen; Ling, Ping
Highlights: Multiple interferences are considered in both steady-state and dynamic signal models. Filters with notches are designed based on the Cosh window to suppress interferences. Filters' characteristics are adaptively adjusted by ESPRIT based frequency analysis. Abstract: Although synchronized phasor measurement unit (PMU) technology is widely applied in transmission networks, conventional PMU algorithms suffer from new challenges (e.g. large frequency deviation, multiple interferences and dynamic behaviors, etc.) if directly applied to distribution networks. On the basis of predecessors' research, this paper presents a comprehensive PMU algorithm, using adaptive filters to simultaneously satisfy the high-precision and dynamic-response requirements of phasor estimation in distribution networks. In this algorithm, out-of-band (OOB) interferences that are difficult to be filtered out, are specifically considered in both steady-state and dynamic signal modelling processes. Based on the models, a finite impulse response (FIR) filter and a Taylor–Fourier transform (TFT) filter that both contains notches at the OOB interferences are elaborately designed and implemented in two parallel channels. With the support of a super-resolution frequency analysis method for signal components, the filters' central frequency and notches' position can be online adaptively adjusted. Finally, the outputs are switched between the two-channel estimations according to a designed transient recognition strategy. Test results in IEEE standard scenarios and some other realistic but severe scenarios demonstrate the effectiveness and reliability of this proposed algorithm.